Analysis of the optimization of resources with Learning Analytics techniques - M-E. Torner; C. Aparicio-Fernández; J-L. Vivancos; M. Cañada-Soriano (Multidisciplinary Journal for Education, Social and Technological Sciences, 2023)
This paper presents an empirical study based on the learning environment through different data analysis tools. The study is applied to the subject of Theory of Machines and Materials Resistance of the Chemical Engineering degree at the Universitat Politècnica de València (Spain), with the aim of being able to understand and optimise with greater knowledge the way of learning taught, to know what is more difficult for the students and to create a more personalised learning environment. In order to achieve this, it is important to have as much information as possible about the use and usefulness of the resources provided to the students as a teacher. Knowing this data will allow us to provide more efficient resources and to change those that, through data analysis, are not being useful to students. The results of this research show how, through applications such as Learning Analytics, greater performance can be obtained in both teaching and learning.